Beyond 'OK' : capturing the student wellbeing of Korean international students : a thesis presented in partial fulfilment of the requirements for the degree of Master in Educational Psychology at Massey University, Albany, New Zealand - Park, Deborah (Massey University, 2015)
Research on international students in New Zealand has found that they face multiple stressors during their sojourn. Currently there is a lack of research on the student wellbeing of very young international students, particularly research that includes their direct voices. This study explored what wellbeing meant to two Korean international students enrolled in a New Zealand primary school. The photovoice method of data collection was used, where the students took photographs of things in their school environment they felt made an important impact on their wellbeing. The students discussed the importance of these photographs during follow up interviews and a focus group. The themes that emerged were compared to the student wellbeing framework developed by the New Zealand Ministry of Education (Education Review Office, 2013b). This study found that wellbeing for the two participants meant being able to form new relationships in New Zealand while maintaining relationships with family in Korea, communicating effectively in English, having the necessary resources and materials to function well in their class, experiencing nature in their physical space, being physically well, having fun, and retaining access to aspects of their own culture. Practical ways that schools and home stay families can support the wellbeing of international students include providing stimulating learning environments, access to adequate language support, peer-pairing programs to encourage the formation of social networks with host-nationals and providing access cultural foods.
Keywords: Koreans; Education (Elementary); Students, Foreign; New Zealand; Psychology